PENGARUH MOTIVASI KERJA KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. TARU MARTANI 1918 YOGYAKARTA - Setiawan, Edi; Yabukon, Rayen (PRIMA EKONOMIKA, 2024)
This research aims to determine the strong influence of WorkMotivation, Compensation, and Work Environment on EmployeePerformance at PT. Taru Martani 1918 Yogyakarta.This type of research uses quantitative research methods. Thepopulation in this study were all employees of PT. Taru Martani 1918Yogyakarta, namely 206 employees and the sample in this study weresome employees of PT. Taru Martani 1918 Yogyakarta, namely 70employees. This research uses primary data sources by distributingquestionnaires directly where respondents only choose the answersprovided. The analytical tests used in this research are researchinstrument tests, classical assumption tests, multiple linear regressionanalysis tests, t and F hypothesis tests, R correlation coefficient tests, andcoefficient of determination tests.The results of the F test show a significant F value of 0.000 <0.05 anda correlation coefficient value of R Square of 0.920. Thus, it can beconcluded that the variables Work Motivation, Compensation and WorkEnvironment have a strong and significant influence on the performance ofPT employees. Taru Martani 1918 Yogyakarta, so H1 is accepted. Basedon the results of the t test, the Work Motivation variable (X1) shows asignificance value of 0.000 < 0.05, so that the Work Motivation variablehas a significant effect on Employee Performance, so H2 is accepted. TheCompensation Variable (X2) shows a significance value of 0.000 < 0.05,so that the Compensation variable has a significant effect on EmployeePerformance, so H3 is accepted. The Work Environment variable (X3)shows a significance value of 0.007 <0.05, so that the Work Environmentvariable has a significant effect on Employee Performance, so H4 isaccepted. The correlation coefficient R is 0.959, which means that theRayen & Edi - Pengaruh Motivasi Kerja, Kompensasi dan LingkunganPage 2independent variable and the dependent variable show a very strongrelationship. The coefficient of determination (Adjusted R Square) obtainedan Adjusted R Square value of 0.917 or 91.7% and the remaining 8.3%was influenced by other variables not examined in this research.